Heuristic Analysis of Functionality and UI/UX in Five Digital Finance Applications - Piisi, Agrianto Timotheus; Kristianto, Budhi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Digital financial applications, such as e-wallets and mobile banking services, have grown significantly in Indonesia as a result of advancements in information technology. However, the user interface (UI) and user experience (UX) of these applications still face several challenges, particularly in navigation, information clarity, and transaction efficiency. Using a heuristic evaluation method, this study aims to compare the functionality and UI/UX quality of five popular digital finance applications in Indonesia: DANA, OVO, LinkAja, myBCA, and Jenius. Three data collection techniques were employed: heuristic evaluation by trained evaluators, analysis of user comments from the Google Play Store, and semi-structured interviews with active users. The most frequently violated heuristic principle was “recognition rather than recall,” followed by issues related to Error Prevention and Flexibility and Efficiency of Use. Among the evaluated applications, LinkAja exhibited the highest number of usability violations, while DANA and OVO recorded the most critical usability issues. Overall, the findings from the three methods were consistent and mutually reinforcing, indicating that usability problems have a direct impact on user experience. This study demonstrates that a triangulated methodological approach is highly effective in identifying and understanding usability issues comprehensively and in providing actionable design recommendations to improve the UI/UX quality of digital financial applications.